The theme of the world diabetes day 2014; healthy living and diabetes; a nephrology viewpoint - Beladi-Mousavi Seyed Seifollah; Bashardoust Bahman; Nasri Hamid; Ahmadi Ali; Tolou-Ghamari Zahra; Hajian Shabnam; Torkamaneh Sara (Society of Diabetic Nephropathy Prevention, 2014)
Annually, on November 14, the world diabetes day (WDD) is celebrated. WDD is a campaign led by the International Diabetes Federation (IDF) and its member associations throughout the world. It was created in 1991 by IDF and World Health Organization (WHO) in response to increasing concerns about the intensifying threat of diabetes worldwide. The WDD 2014 organization marks the first of a three-year (2014-16) emphasis on "healthy living and diabetes". Replacement of whole grain and cereal-based foods with refined grains in diet planning could be an operative and practical strategy in type II diabetic patients. This strategy beyond the development of glycemic control, leads to more benefits for management of other features of diabetes, diminution of diabetes-induced metabolic disorders, and prevents long-term complications especially diabetic kidney disease and cardiovascular disease.